Current dilemmas in the diagnosis and management of follicular thyroid tumors. Issue 5 (2nd September 2016) - Renard, Marine; Lloveras, Belén; Flores, Juana; Puig, Jaume; Benaiges, David; Sitges-Serra, Antonio
ABSTRACT: Follicular carcinoma (FTC) is a relatively uncommon type of differentiated thyroid carcinoma. Guidelines have often dealt with FTC and papillary thyroid cancer as a single disease. Over the last decade, however, a better understanding of these two types of thyroid cancer indicates that they cannot be analysed together. Neither ultrasonography nor fine-needle aspiration cytology can provide a clear distinction between FTC and follicular adenoma. New molecular diagnostic techniques may be used to identify a subpopulation of follicular neoplasms with a low probability of being malignant. Diagnostic surgery—usually hemithyroidectomy- is recommended for most thyroid follicular lesions without a certain preoperative diagnosis. If FTC is diagnosed most—perhaps not all- patients will require a completion thyroidectomy. While widely invasive FTC usually does not pose diagnostic or therapeutic doubts, consensus on the diagnosis of non-invasive follicular lesions is still lacking. Prognosis of FTC is mostly dependent on local invasion and distant metastasis that, in turn, correlate with tumor size.